Interactive jamming with Shimon: a social robotic musician - Weinberg, Gil; Raman, Aparna; Mallikarjuna, Trishul (2009 4th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2009)
The paper introduces Shimon: a socially interactive and improvisational robotic marimba player. It presents the interaction schemes used by Shimon in the realization of an interactive musical jam session among human and robotic musicians.